The impact of research and development tax incentives on Colombia's manufacturing sector : what difference do they make? - Mercer-Blackman, Valerie (IMF working paper ;, 2008)
Do tax incentives for science and technology stimulate additional investment? We use detailed data on applications and acceptances for R & D tax incentives, a special survey, and for the first time, the science and technology module from the 2000-2002 Survey of Manufacturers database in Colombia to analyze this question. We estimate the effect of the R & D tax deduction instituted in Colombia using Zellner's Seemingly Unrelated Regressions method, and find that the elasticity of demand of R & D investment in manufacturing is quite high in Colombia compared to other countries, particularly for smaller firms, but that the direct benefit from existing policies is minimal. Overall, the results of the paper suggest that there is a great potential for such incentives to promote R & D investment in Colombia, but in their current form, they fail to target those firms that could benefit the most.